Psychological Wellbeing and Employability of Retrenched Workforce During COVID-19: A Qualitative Study Exploring the Mitigations for Post Pandemic Recovery Phase - Guek-Nee Ke; Dasha Grajfoner; Stephen Carter; Nicole DeLima; Rozainee Khairudin; Wee-Yeap Lau; Khalil Anwar Kamal; Shen Chieng Lee (Frontiers in Public Health, 2022)
The ongoing COVID-19 pandemic has triggered several employment-related issues, followed by different response strategies. With retrenchment measures being a common response strategy during economic downturns, many individuals have been faced with unemployment. This study aimed to explore the effect of the COVID-19 pandemic related retrenchment on the psychological wellbeing of the Malaysian workforce, using a qualitative research approach and based on the Latent-deprivation Model. A purposive sample of 30 retrenched participants was interviewed via telephone during Malaysia's Movement Control Order (MCO). Thematic analysis was subsequently conducted to identify key themes in the data set. Six themes emerged from the thematic analysis: (1) Retrenchment leading to the deterioration of psychological wellbeing; (2) Unemployment, financial strain and economic uncertainty; (3) Emotions related to the COVID-19 virus; (4) Coping with lifestyle change; (5) Recommendations to improve the psychological wellbeing and mental health of the retrenched workforce, and (6) Career and financial support at the recovery phase. The present study provides valuable insight into the wellbeing of retrenched workforce who are forced to cope with both unemployment and a global pandemic, and workforce perspectives regarding types of support needed during the recovery phase.